Preparation and characterization of a novel rechargeable antibacterial polyurethane sponge foam substrate modified with chlorinated N-halamine for efficient disinfection - Ali Ashraf Derakhshan; Ali Akbar Zinatizadeh; Ali Rostami; Fariba Oulad; Khosrow Chehri; Mozhgan Fatahi Dehpahni (Scientific Reports)
Abstract This research offers a simple and convenient strategy for surface decoration of polyurethane sponge foam through the covalent attachment of 5,5-dimethylhydantoin as an N-halamine precursor using 1,6-hexamethylene diisocyanate as a crosslinking agent. After hypochlorite bleach treatment, the N-H bonds in the 5,5-dimethylhydantoin moieties on the polyurethane sponge foam surface change into N-Cl bonds. This modification enhances antibacterial performance against both Gram-positive and Gram-negative bacteria. The washing stability of the prepared Cl-DMH-PUSF substrates was studied after 20 rinsing cycles using the DPD tablet test. The results showed that no active chlorine was released from the Cl-DMH-PUSF substrate after multiple washing processes, implying the strong stability of the active chlorine on the N-halamine surface. To characterize the synthesized antiseptic samples, field emission scanning electron microscopy (FESEM) and energy dispersive X-ray analysis were applied. FESEM images revealed a collection of needle-shaped nanoparticles on the Cl-DMH-PUSF surface, which could act as a needle in contact with bacteria and contribute to pathogen death. This approach is innovative as it uses commercial polyurethane sponge foam modified under mild conditions to produce rechargeable antibacterial substrates with unique nano-coral structures, enabling both chemical and mechanical antibacterial actions.